2012
DOI: 10.1007/s10965-012-9862-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity and crystallization behavior of PVDF/PMMA/TiO2(SiO2) composites prepared by in situ polymerization

Abstract: Composites with enhanced hydrophilicity were prepared by adding TiO 2 or SiO 2 nanoparticles during the in situ polymerization of methyl methacrylate (MMA) in poly(vinylidene fluoride) (PVDF). The hydrophilicities of the PVDF/PMMA/TiO 2 (SiO 2 ) composites generated in this manner were characterized by contact angle measurements and atomic force microscopy (AFM). The hydrophilicity was dependent on nanoparticle content; it gradually increased with increasing TiO 2 (or SiO 2 ) content when the TiO 2 (or SiO 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…The TiO 2 concentration generally ranges between 0 and 5 wt% by according to various studies reported in literature [ 45 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. In the present research, membranes containing different amounts of TiO2 (0.12, 0.25 and 0.5 wt%) were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…The TiO 2 concentration generally ranges between 0 and 5 wt% by according to various studies reported in literature [ 45 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. In the present research, membranes containing different amounts of TiO2 (0.12, 0.25 and 0.5 wt%) were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…3a. This indicated that the addition of CNCs did not change the crystal phase of PVDF (Zhao et al 2012). However, at higher wave number regions (Fig.…”
Section: Static Water Contact Anglementioning
confidence: 85%
“…However, the hydrophobic nature of PVDF usually renders low permeability and poor antifouling ability, which restricts its expanded uses (Ma et al 2007). To overcome the hydrophobic nature, introducing some hydrophilic groups was utilized via surface modification (Rana and Matsuura 2010), in situ polymerization (Zhao et al 2010(Zhao et al , 2012, and bulk graft copolymerization (Liu et al 2003). Among these methods, blending is the most versatile and straightforward processing method.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of TiO 2 ‐polymer composites have been described in the literature, such as TiO 2 ‐poly(styrene‐divinylbenzene)/maleic anhydride, TiO 2 ‐polypirrole, TiO 2 ‐PMMA, TiO 2 /poly (amide‐imide), TiO 2 /P(St‐ co ‐DVB)‐MAA, TiO 2 /polystyrene, TiO 2 (SiO 2 )/PVDF/PMMA, TiO 2 /(VAc‐BuA), TiO 2 /PET …”
Section: Introductionmentioning
confidence: 99%